Representing Greenland ice sheet freshwater fluxes in climate models. Issue 15 (6th August 2015) - Lenaerts, Jan T. M.; Le Bars, Dewi; van Kampenhout, Leo; Vizcaino, Miren; Enderlin, Ellyn M.; van den Broeke, Michiel R.
Abstract Here we present a long‐term (1850–2200) best estimate of Greenland ice sheet (GrIS) freshwater runoff that improves spatial detail of runoff locations and temporal resolution. Ice discharge is taken from observations since 2000 and assumed constant in time. Surface meltwater runoff is retrieved from regional climate model output for the recent past and parameterized for the future based on significant correlations between runoff and midtropospheric (500 hPa) summer temperature changes over the GrIS. The simplicity of this approach enables assimilation of meltwater runoff into coupled climate models, which is demonstrated here in a case study with the medium‐resolution (1°) Community Earth System Model. The model results suggest that the decrease in Atlantic Meridional Overturning Circulation (AMOC) is dominated by warming of the surface ocean and enhanced GrIS freshwater forcing leads to a slightly enhanced (−1.2 sverdrup in the 21st century) weakening of the AMOC.